Degradation of 17 Benzodiazepines by the UV/H2O2 Treatment - You, Wen-Dan; Ye, Pu; Yang, Bin; Luo, Xin; Fang, Jie; Mai, Zi-Tian; Sun, Jian-Liang (Frontiers in Environmental Science, 2021)
Benzodiazepines are one group of psychoactive drugs widely detected in water environments, and their persistence during conventional wastewater treatment has raised great concerns. Here we investigated the degradation of 17 benzodiazepines in water by UV/H2O2 treatment. The results showed that the UV/H2O2 treatment significantly increased the degradation of 17 benzodiazepines in phosphate buffer solutions at pH 7.0. This can be attributed to the high reactivity of hydroxyl radicals (·OH) towards benzodiazepines with second-order rate constants of 3.48×109 M-1 s-1‒2.44×1010 M-1 s-1. The degradation of alprazolam, a typical benzodiazepine, during the UV/H2O2 treatment was increased with the increasing H2O2 dosage. The solution pH influenced the alprazolam degradation significantly, with the highest degradation at pH 7.0. Water matrix, such as anions (Cl-, HCO3-, NO3-) and humic acid, decreased the degradation of alprazolam by UV/H2O2 treatment. Based on the degradation products identified using quadrupole time-of-flight mass spectrometer, the degradation mechanisms of alprazolam by UV/H2O2 treatment were proposed, and hydroxylation induced by ·OH was the main reaction pathway. The degradation of 17 benzodiazepines by UV/H2O2 treatment in wastewater treatment plant effluent and river water was lower than that in phosphate buffer solutions. The results showed that the benzodiazepine psychoactive drugs in natural water can be effectively removed by the UV/H2O2 treatment.